The origins and evolution of social commerce: enhancing e-commerce platforms with social features - Fanárraga Olivares, Lucia Isabel (2022)
With technological development and digital transformation, the social commerce model has quickly become the best strategy for delivering a superior shopping experience. Although the history and evolution of the model can be studied, the future of the model is uncertain and may become an even more complex and diverse concept. However, new technologies and tendencies such as Web 3.0, the metaverse, and NFTs may give us a glimpse of the future. In this article, an analysis was conducted on the current scenario and evolution of the model based on the article "A systematic review on social commerce" by Esmaeili and Alireza, which discloses results from 2014 to 2017. Fifty-two journal articles were selected to update the answers to the 5 W´s model presented in the article mentioned above. The results revealed not only the evolution of the model but also the evolution of the approach of the companies when building their social commerce platform.